ABDIMAS USAHA LADRANG DESA BAJERA, SELEMADEG, TABANAN - Mendra, Ni Putu Yuria; Praganingrum, Tjokorda Istri (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2018)
Chips is one type of snack loved by people both lower, middle, and upper. Chips are many kinds of one of them there is called onion chips, which is more famous by the name